Factors Associated with Early Career Research Productivity after Ophthalmology Residency - Wieder, Matthew S.; He, Catherine H.; Pahl, Daniel A.; Parsikia, Afshin; Mbekeani, Joyce N. (Journal of Academic Ophthalmology, 2022)
Background Few studies have evaluated associations between ophthalmology trainee characteristics and performance with postgraduate research productivity.Purpose This article evaluates factors associated with post-residency research productivity among U.S. ophthalmology graduates.Methods Publicly available information of residents graduating between 2009 and 2014 from 30 randomly selected U.S. ophthalmology programs was collected from June to September 2020. Differences in publications between the 5 years post-residency and pre-residency/residency period were used as metrics of productivity. Residents with incomplete records were excluded.Results A total of 758 of 768 residents, 306 females (40.4%) and 452 males (59.6%), met inclusion criteria. The mean (standard deviation [SD]) number of pre-residency publications was 1.7 (4.0), residency was 1.3 (2.2), and post-residency was 4.0 (7.3). Mean (SD) H-index was 4.2 (4.9). Top-ranked residency (p = 0.001), Alpha Omega Alpha (AOA) medical honor status (p = 0.002), U.S. medical school graduates (p < 0.001), and academic career (p < 0.001) were all associated with higher pre-/post-residency mean publication difference. Pursuing fellowship training also was associated with higher total publications (p < 0.001). Of all pre-residency degrees, PhD had the greatest odds of high postgraduate publications (defined as > 4). There was a positive correlation between both pre-residency/residency and post-residency publications (rho = 0.441; p < 0.001) and between mean difference of pre-residency/post-residency publications for residents at a program and that program's Doximity rank (rho = 0.497; p < 0.001). Multivariate logistic regression revealed, academic career choice (odds ratio [OR] = 3.38; p < 0.001), Heed fellowship (OR = 3.12; p = 0.031), > 2 residency publications (OR = 2.89; p < 0.001), AOA status (OR = 2.0; p = 0.004), and top-ranked residency programs (OR = 1.89; p = 0.007), had greatest odds of > 4 postgraduation publications.Conclusion Higher post-residency productivity was associated with multiple factors, with choice of an academic career, Heed fellowship, and residency productivity playing key roles.
Keywords: ophthalmology; residency; publication; research productivity; Doximity rank